2011
DOI: 10.1016/j.bpj.2011.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of DNA/PEI Complexes: Effect of PEI Branching and Protonation State

Abstract: Complexes formed by DNA and polyethylenimine (PEI) are of great research interest because of their application in gene therapy. In this work, we carried out all-atom molecular dynamics simulations to study eight types of DNA/PEI complexes, each of which was formed by one DNA duplex d(CGCGAATTCGCG)(2) and one PEI. We used eight different PEIs with four different degrees of branching and two protonation ratios of amine groups (23% and 46%) in the simulations to investigate how the branching degree and protonatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
165
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(177 citation statements)
references
References 41 publications
10
165
2
Order By: Relevance
“…and PEI50 binding to DNA reported here agree with previous simulational studies, 21,22 and experiments 59 where deprotonated PEI is was more prone to bind to DNA grooves, and it was suggested that this bind-ing is driven by the release of water. In contrast, protonated PEI preferred DNA backbone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…and PEI50 binding to DNA reported here agree with previous simulational studies, 21,22 and experiments 59 where deprotonated PEI is was more prone to bind to DNA grooves, and it was suggested that this bind-ing is driven by the release of water. In contrast, protonated PEI preferred DNA backbone.…”
Section: Discussionsupporting
confidence: 92%
“…Monte Carlo simulations of PEI protonation confirm this configuration, 24 and similar choices for PEI protonation degree and configuration have previously been used for MD simulations of PEI. 21 The molecular structures of the polycations are shown in Fig. 1 First, the DNA strand was placed in a simulation box of 10×10×10 nm 3 together with two polycation molecules (two PLLs, PEI50s or PEI25s) and solvated with water.…”
Section: Methods and Simulated Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…26) Our molecular dynamics studies also showed that a 600 Da branched PEI binds to 4 base pairs in the major groove of DNA. 32) This corresponds to l=8, which was the parameter used in excluded site model in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that PEI with a molecular weight of 800 Da cannot condense DNA efficiently. 46 Furthermore, Sun et al 47 reported that a high protonation ratio of the amino groups in PEI results in the formation of more stable complexes with DNA, but the degree of branching has lesser effect on DNA binding. The higher IFN-α production by flake-shell SiO 2 nanoparticles coated with PEI-600 is likely caused by increased affinity of CpG oligodeoxynucleotide molecules for TLR9, which results from the loose condensation of CpG oligodeoxynucleotide molecules.…”
mentioning
confidence: 99%